Lack of evidence to favor specific preventive interventions in psychosis: a network meta‐analysis. Issue 2 (June 2018) - Davies, Cathy; Cipriani, Andrea; Ioannidis, John P.A.; Radua, Joaquim; Stahl, Daniel; Provenzani, Umberto; McGuire, Philip; Fusar‐Poli, Paolo
Abstract : Preventing psychosis in patients at clinical high risk may be a promising avenue for pre‐emptively ameliorating outcomes of the most severe psychiatric disorder. However, information on how each preventive intervention fares against other currently available treatment options remains unavailable. The aim of the current study was to quantify the consistency and magnitude of effects of specific preventive interventions for psychosis, comparing different treatments in a network meta‐analysis. PsycINFO, Web of Science, Cochrane Central Register of Controlled Trials, and unpublished/grey literature were searched up to July 18, 2017, to identify randomized controlled trials conducted in individuals at clinical high risk for psychosis, comparing different types of intervention and reporting transition to psychosis. Two reviewers independently extracted data. Data were synthesized using network meta‐analyses. The primary outcome was transition to psychosis at different time points and the secondary outcome was treatment acceptability (dropout due to any cause). Effect sizes were reported as odds ratios and 95% confidence intervals (CIs). Sixteen studies (2, 035 patients, 57% male, mean age 20.1 years) reported on risk of transition. The treatments tested were needs‐based interventions (NBI); omega‐3 + NBI; ziprasidone + NBI; olanzapine + NBI; aripiprazole + NBI; integrated psychological interventions; family therapy + NBI; D‐serine + NBI; cognitive behavioural therapy, French & Morrison protocol (CBT‐F) + NBI; CBT‐F + risperidone + NBI; and cognitive behavioural therapy, van der Gaag protocol (CBT‐V) + CBT‐F + NBI. The network meta‐analysis showed no evidence of significantly superior efficacy of any one intervention over the others at 6 and 12 months (insufficient data were available after 12 months). Similarly, there was no evidence for intervention differences in acceptability at either time point. Tests for inconsistency were non‐significant and sensitivity analyses controlling for different clustering of interventions and biases did not materially affect the interpretation of the results. In summary, this study indicates that, to date, there is no evidence that any specific intervention is particularly effective over the others in preventing transition to psychosis. Further experimental research is needed.